2023
DOI: 10.1002/advs.202301104
|View full text |Cite
|
Sign up to set email alerts
|

Fast Delivery of Multifunctional NIR‐II Theranostic Nanoaggregates Enabled by the Photoinduced Thermoacoustic Process

Abstract: Multifunctional nanoaggregates are widely used in cancer phototheranostics. However, it is challenging to construct their multifunctionality with a single component, and deliver them rapidly and efficiently without complex modifications. Herein, a NIR‐absorbing small molecule named TBT‐2(TP‐DPA) is designed and certify its theranostic potentials. Then, their nanoaggregates, which are simply encapsulated by DSPE‐PEG, demonstrate a photothermal efficiency of 51% while keeping a high photoluminescence quantum yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The DLS data revealed that the average sizes of the BTT NPs and BTB NPs were 194 and 153 nm, respectively, which were beneficial for the accumulation of the nanoparticles at inflammatory or tumor sites by virtue of the enhanced permeability and retention (EPR) effect. 55,56 The photophysical data of the two nanoparticles showed that the maximum absorption peaks of the BTT NPs and BTB NPs were 640 and 756 nm (Figure 2b), respectively. Compared to their maximal absorption peaks in THF solution, both nanoparticles exhibited significant red-shifted absorption peaks.…”
Section: Preparation and Characterization Of Nanoparticlesmentioning
confidence: 99%
“…The DLS data revealed that the average sizes of the BTT NPs and BTB NPs were 194 and 153 nm, respectively, which were beneficial for the accumulation of the nanoparticles at inflammatory or tumor sites by virtue of the enhanced permeability and retention (EPR) effect. 55,56 The photophysical data of the two nanoparticles showed that the maximum absorption peaks of the BTT NPs and BTB NPs were 640 and 756 nm (Figure 2b), respectively. Compared to their maximal absorption peaks in THF solution, both nanoparticles exhibited significant red-shifted absorption peaks.…”
Section: Preparation and Characterization Of Nanoparticlesmentioning
confidence: 99%
“…The in vivo NIR fluorescence imaging represents an emerging biomedical imaging technique with well-established safety and methodology. , Compared to other methods for biological tissue imaging, NIR imaging offers substantial advantages. One notable advantage of NIR imaging is nonionizing radiation, which eliminates the risk of tissue damage, thereby enabling the possibilities of kinetic imaging. , The longer wavelengths of NIR fluorescence result in reduced light scattering and biomolecular absorption and can penetrate deep into tissues. , In addition, NIR imaging also benefits from the low autofluorescence exhibited by biological tissues at long wavelengths, ensuring a high signal-to-noise ratio within the organism. , Over the past decade, NIR fluorescence imaging has focused on traditional NIR-I imaging (700–900 nm), while recent advances have been made in the field of NIR-II imaging (1000–1700 nm). , By further reductions in scattering, absorption, and organismal autofluorescence, in vivo , NIR-II fluorescence imaging outperforms imaging in NIR-I imaging capabilities. NIR-II imaging has been used for medical diagnosis, tumor therapy, and photothermal imaging. , However, near-infrared two-region sensors with stimulus-responsive properties are lacking, and such sensors are seldom applied to the detection of environmental substances.…”
Section: Introductionmentioning
confidence: 99%
“…Indocyanine green (ICG), organic luminogens hold significant promise for bioimaging applications compared to inorganic counterparts . Common approaches to design organic NIR-II dyes include conjugation extension and donor–acceptor (D-A) engineering . However, extended conjugation and D–A structures often lead to strong intermolecular π–π and D–A interactions, resulting in aggregation-caused quenching (ACQ). , Consequently, many NIR-II dyes suffer from a low fluorescence quantum yield (QY).…”
mentioning
confidence: 99%